Subunit Interaction Differences Between the Replication Factor C Complexes in Arabidopsis and Rice - Chen, Yueyue; Qian, Jie; You, Li; Zhang, Xiufeng; Jiao, Jinxia; Liu, Yang; Zhao, Jie (Frontiers in Plant Science, 2018)
Replication factor C (RFC) is a multisubunit complex that opens the sliding clamp and loads it onto the DNA chain in an ATP-dependent manner and is thus critical for high-speed DNA synthesis. In yeast (Saccharomyces cerevisiae) and humans, biochemical studies and structural analysis revealed interaction patterns between the subunits and architectures of the clamp loaders. Mutations of ScRFC1/2/3/4/5 lead to loss of cell viability and defective replication. However, the functions of RFC subunits in higher plants are unclear, except for AtRFC1/3/4, and the interaction and arrangement of the subunits have not been studied. Here, we identified rfc2-1/+, rfc3-2/+ and rfc5-1/+ mutants in Arabidopsis, and found that embryos and endosperm arrested at the 2/4-celled embryo proper stage and 6-8 nuclei stages, respectively. Subcellular localization analysis revealed that AtRFC1 and OsRFC1/4/5 proteins were localized in the nucleus, while AtRFC2/3/4/5 and OsRFC2/3 proteins were present both in the nucleus and cytoplasm. By using yeast two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) techniques, we demonstrated the interactions of Arabidopsis and rice (Oryza sativa) RFC subunits, and proposed arrangements of the five subunits within the RFC complex, which were AtRFC5-AtRFC4-AtRFC3/2-AtRFC2/3-AtRFC1 and OsRFC5-OsRFC2-OsRFC3-OsRFC4-OsRFC1, respectively. In addition, AtRFC1 could interact with AtRFC2/3/4/5 in the presence of other subunits, while OsRFC1 directly interacted with the other four subunits. To further characterize the regions required for complex formation, truncated RFC proteins of the subunits were created. The results showed that C-termini of the RFC subunits are required for complex formation. Our studies indicate that the localization and interactions of RFCs in Arabidopsis and rice are distinctly discrepant.